Systematic review of early English literacy in ELL children : what do we know from a decade of research - Noor Asma Iffah Zakaria,; Mohd Rashid Mohd Saad,; Mariani Md Nor, (Penerbit Universiti Kebangsaan Malaysia, 2021)
Early literacy is an integral aspect of young children’s learning. This review synthesizes existing empirical research evidence from the past decade, focusing on ELL children’s (aged 4 to 6 years) early English language literacy learning and the prevailing trends in the published literature. They were sourced mainly from three prominent databases. Manual selection of highly-cited studies was used as a complementary technique. Systematic exclusion and inclusion were performed and yielded 31 credible studies. The results report on researchers’ theorizing of early English literacy, dimensions of the body of knowledge, and research methodologies. The predictors and outcomes were examined within the lens of theoretical framework. To identify the emerging trends, the studies were analysed qualitatively. The findings were discussed in light of three main trends: (i) the apparent needs for an early English literacy model which captures both the concept of early literacy acquisition and second language learning, (ii) future research to acknowledge the multifaceted phenomenon of early literacy acquisition by employing nested research approach in a cross-discipline scope of research, and (iii) multiple ecological factors as important sources of individual differences. Despite the strength of the review approach to the past study identification, there are several limitations that should be considered. Among others, the representation of the children population in the selected studies which befalls heavily on certain geographical regions could cause bias in the coverage of knowledge.